1991
DOI: 10.1093/oxfordjournals.annonc.a058029
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II study of ondansetron as antiemetic prophylaxis in patients receiving carboplatin for advanced ovarian cancer

Abstract: Thirty four patients who were receiving carboplatin 400 mg/m2 for advanced epithelial ovarian cancer were treated with ondansetron antiemetic prophylaxis. Ondansetron was given as 4 mg oral +4 mg iv 30 minutes prior to carboplatin followed by 8 mg oral tds for 5 days. Of the evaluable patients complete or major control of emesis on day one was achieved in 94% of previously untreated patients and 81% of patients refractory to conventional antiemetic therapy. For the 5 day period as a whole 88% of untreated pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

1996
1996
2001
2001

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
0
4
1
Order By: Relevance
“…However, the results of this study show better efficacy than previously reported by Smith et al [6] and Harvey et al [7] where less than optimal doses of ondansetron com binations were administered. Similar results have, how ever, been observed in other studies where patients re ceived other non-cisplatin-based chemotherapy regimens.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…However, the results of this study show better efficacy than previously reported by Smith et al [6] and Harvey et al [7] where less than optimal doses of ondansetron com binations were administered. Similar results have, how ever, been observed in other studies where patients re ceived other non-cisplatin-based chemotherapy regimens.…”
Section: Discussioncontrasting
confidence: 62%
“…Two small studies have also been reported, one conducted in the United Kingdom and one in New Zea land [6,7], which suggest that although good response rates were observed during the acute phase of treatment, some 40-50% of patients experienced prolonged symp toms of emesis over the 4 days following carboplatin che motherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the urinary excretion of 5-HIAA fol lows a similar time course to the pattern of emesis [ 15]. As occurs with cyclophosphamide, ondansetron can prevent both the 'acute' and 'delayed' phase of carboplatininduced emesis [16].…”
Section: Carboplatin-lnduced Em Esismentioning
confidence: 99%
“…Most of the patients suffered from severe emesis with a mean number of 13.5 vomiting episodes per patient. Data from 79 patients included in 3 anti-emetic trials using ondanse tron for the prevention of carboplatin-induced emesis were identified in a Medline literature search [11][12][13]. Although the numbers are small, there is clear evidence that ondansetron is efficacious in reducing carboplatin-induced emesis.…”
Section: Severity and Pattern Of Carboplatin-induced Em Esismentioning
confidence: 99%
“…The publications of these stud ies of 'noncisplatin-induced emesis' do not provide enough detailed data for a subgroup analysis of carboplatin-treated patients. A Medline search revealed only 3 studies of anti-emetic treatment for patients receiving car boplatin [11][12][13] . 3).…”
Section: Introductionmentioning
confidence: 99%